2018
DOI: 10.3389/fendo.2018.00475
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Interval Training Is Equivalent to Moderate-Intensity Continuous Training for Short- and Medium-Term Outcomes of Glucose Control, Cardiometabolic Risk, and Microvascular Complication Markers in Men With Type 2 Diabetes

Abstract: We sought to determine the efficacy of 12 weeks high-intensity interval training (HIIT), compared to moderate-intensity continuous training (MICT) on glucose control, cardiometabolic risk and microvascular complication markers in men living with type 2 diabetes (T2D). Both modalities were combined with resistance training (RT). Additionally, the study aimed to determine the medium-term durability of effects. After a 12-week, thrice weekly, training intervention incorporating either MICT+RT (n = 11) or HIIT+RT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 85 publications
0
52
0
1
Order By: Relevance
“…It has been shown that these are even more beneficial for improving physical and mental health outcomes in healthy and diabetic populations. 19,20 HIIT protocols enable individuals who exercise to maintain at maximal or near maximal oxygen uptake (T@VO2max) for long periods of time, because a potent stimulus elicits both central (oxygen transport) and peripheral (oxygen utilization) adaptations for VO2max improvement. 7,21,22 Many different components of HIIT such as work intensity, bout duration, number of repetitions, and training periodization have been shown to have substantial influence on T@VO2max.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…It has been shown that these are even more beneficial for improving physical and mental health outcomes in healthy and diabetic populations. 19,20 HIIT protocols enable individuals who exercise to maintain at maximal or near maximal oxygen uptake (T@VO2max) for long periods of time, because a potent stimulus elicits both central (oxygen transport) and peripheral (oxygen utilization) adaptations for VO2max improvement. 7,21,22 Many different components of HIIT such as work intensity, bout duration, number of repetitions, and training periodization have been shown to have substantial influence on T@VO2max.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…The most commonly observed primary outcome measure in HIIT studies is a change in peak oxygen consumption (VO 2 peak) as an indirect measure of improvement in cardiovascular disease risk [39]. Various other improvements in cardiometabolic health markers are also observed in trials investigating HIIT in adults with overweight/obesity, including reductions in systolic and diastolic blood pressure [40, 41], reversal of dyslipidemia [42, 43], improvements in insulin resistance, glycated haemoglobin (HbA1c) and fasting blood glucose concentrations [4345]. The improvements in cardiometabolic risk factors are observed following both short term (< 12 weeks) and long term (> 12 weeks) participation in HIIT interventions despite no significant change in body composition [40].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 753 articles were excluded, resulting in 60 that met the selection criteria and 5603 enrolled participants (of whom 5261 were analyzed). 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ...…”
Section: Resultsmentioning
confidence: 99%
“…The durations of follow-up ranged from 1 to 60 months (median, 12 months). A total of 21 studies were from Western Europe, 25 , 27 , 41 , 54 , 61 , 62 , 65 , 72 , 81 , 82 , 84 11 from North America, 25 , 27 , 41 , 54 , 61 , 62 , 65 , 72 , 81 , 82 , 84 9 from East Asia, 29 , 38 , 39 , 44 , 51 , 52 , 60 , 66 , 68 5 from South America, 28 , 69 , 78 , 79 , 83 5 from Western Asia, 28 , 69 , 78 , 79 , 83 and 3 each from Africa, 35 , 50 , 76 the Pacific, 26 , 42 , 75 and Eastern Europe. 45 , 74 , 80 …”
Section: Resultsmentioning
confidence: 99%